ASSESSMENT OF FAMILY BURDEN, SOCIAL SUPPORT, AND QUALITY OF LIFE AMONG PARENTS OF CHILDREN WITH MULTIPLE DISABILITIES - Kori, Ashok S.; Asagi, Renuka E. (International Journal of Research -GRANTHAALAYAH, 2025)
The increasing prevalence of childhood disabilities across various socio-cultural settings due to various reasons necessitates a deeper understanding of the psychosocial implications for families. The family, especially the parents, often becomes the primary source of care and advocacy for a child with disabilities. This caregiving role brings about significant physical, emotional, financial, and social challenges. The findings discussed in this article are drawn from data collected in the community, with a focus on socio-demographic condition of parents of children with disabilities and from social work perspective. The study findings are from pilot study.